Heroes at home - Wells, Zeb (Marvel, 2020)
Short, mostly wordless comic panels imagine what several Marvel superheroes might do while "sheltering in place" at home during the COVID-19 pandemic--including Spider-Man, Captain America, Captain Marvel, and Thor.